Conservation Regime and Local Population Ecology of Sarus Crane (Grus antigone antigone) in West-Central Region of Nepal - Aryal, Achyut; Shrestha, Tej Kumar; Sen, Dhriti Shree; Upreti, Baburam; Gautam, Nawaraj (Journal of Wetlands Ecology, 2009)
The research explores the current and future conservation regime, and local population ecology of globally threatened water bird Sarus Crane (Grus antigone antigone) in Rupandehi, and Kapilvastu districts of Nepal. The study strongly recommended to declaring certain areas of these districts as a Sarus Crane Conservation Area (SCCA) for its future better management regime. A total of 168 Sarus Cranes were recorded in the area (100 in Rupandehi and 68 in Kapilvastu district). Overall population density of Sarus Crane was 9.3 individual/100 km2. Seventy percent of Sarus Cranes were using farmland while 30% using wetland as a regular habitat. Current threats to the Sarus Crane population are habitat loss and degradation, high electrical cable line, sugar cane cultivation surrounding the Sarus crane habitat, dam and cementation in water canal, water pollution due to nutrients and chemical leakage in water bodies, environmental contamination and other anthropogenic causes. Key words: Sarus crane, threatened, low land, wetlands DOI: 10.3126/jowe.v3i0.2224 Journal of Wetlands Ecology, (2009) Vol. 3, pp 1-11